Mr Katō plays family (Forge/Tor Publishing Group, 2023)
"Milena Michiko Flašar's Mr Katō Plays Family is an eccentric second-lease-on-life novel for fans of A Man Called Ove and Beautiful World, Where Are You. Mr Katō-a curmudgeon and recent retiree-finds his only solace during his daily walks, where he wonders how his life went wrong and daydreams about getting a dog (which his wife won't allow). During one of these walks, he is approached by a young woman. She calls herself Mie, and invites him to join her business Happy Family, where employees act as part-time relatives or acquaintances for clients in need, for whatever reason, if only for a day. At first reluctant, but then intrigued, he takes the job without telling his wife or adult children. Through the many roles he takes on, Mr Katō rediscovers the excitement and spontaneity of life, and re-examines his role in his own family. Using lessons learned with his "play families," he strives to reconnect with his loved ones, to become the father and husband they deserve, and to live the life he's always wanted"--

Septology (Transit Books, 2022)
What makes us who we are? And why do we lead one life and not another? Asle, an aging painter and widower who lives alone on the southwest coast of Norway, is reminiscing about his life. His only friends are his neighbor, Åsleik, a traditional fisherman-farmer, and Beyer, a gallerist who lives in the city. There, in Bjørgvin, lives another Asle, also a painter but lonely and consumed by alcohol. Asle and Asle are doppelgängers--two versions of the same person, two versions of the same life, both grappling with existential questions about death, love, light and shadow, faith and hopelessness. The three volumes of Jon Fosse's Septology--The Other Name, I is Another, and A New Name--collected here for the first time, are a transcendent exploration of the human condition, and a radically other reading experience--incantatory, hypnotic, and utterly unique.
I-II. The other name , III-V. I is another , VI-VII. A new name.

The words that remain: a novel (New Vessel Press, 2023)
"A letter has beckoned to Raimundo since he received it over fifty years ago from his youthful passion, handsome Cícero. But having grown up in an impoverished area of Brazil where the demands of manual labor thwarted his becoming literate, Raimundo has long been unable to read. As young men, he and Cícero fell in love, only to have Raimundo's father brutally beat his son when he discovered their affair. Even after Raimundo succeeds in making a life for himself in the big city, he continues to be haunted by this secret missive full of longing from the distant past. Now at age seventy-one, he at last acquires a true education and the ability to access the letter. Exploring Brazil's little-known hinterland as well its urban haunts, this is a sweeping novel of repression, violence, and shame, along with their flip side: survival, endurance, and the ultimate triumph of an unforgettable figure on society's margins. The Words That Remain explores the universal power of the written word and language, and how they affect all our relationships." --$c Back cover.

The book of Charlie: wisdom from the remarkable American life of a 109-year-old man (Center Point Large Print, Simon & Schuster, 2023)
"When a veteran Washington journalist moved to Kansas, he met a new neighbor who was more than a century old. Little did he know that he was beginning a long friendship -- and a profound lesson in the meaning of life. Charlie White was no ordinary neighbor. Born before radio, Charlie lived long enough to use a smartphone. When a shocking tragedy interrupted his idyllic boyhood, Charlie mastered survival strategies that reflect thousands of years of human wisdom. Thus armored, Charlie's sense of adventure carried him on an epic journey across the continent, and later found him swinging across bandstands of the Jazz Age, racing aboard ambulances through Depression-era gangster wars, improvising techniques for early open-heart surgery, and cruising the Amazon as a guest of Peru's president. David Von Drehle came to understand that Charlie's resilience and willingness to grow made this remarkable neighbor a master in the art of thriving through times of dramatic change. As a gift to his children, he set out to tell Charlie's secrets. The Book of Charlie is a gospel of grit -- the inspiring story of one man's journey through a century of upheaval. The history that unfolds through Charlie's story reminds you that the United States has always been a divided nation, a questing nation, an inventive nation -- a nation of Charlies in the rollercoaster pursuit of a good and meaningful life."--

Be mine (Frank Bascombe novels, 5, 1, 2023)
"From Pulitzer Prize winner Richard Ford: the final novel in the world of Frank Bascombe, one of the most indelible characters in American literature Over the course of four celebrated works of fiction and almost forty years, Richard Ford has crafted an ambitious, incisive, and singular view of American life as lived. Unconstrained, astute, provocative, often laugh-out-loud funny, Frank Bascombe is once more our guide to the great American midway. Now in the twilight of life, a man who has occupied many colorful lives-sportswriter, father, husband, ex-husband, friend, real estate agent--Bascombe finds himself in the most sorrowing role of all: caregiver to his son, Paul, diagnosed with ALS. On a shared winter odyssey to Mount Rushmore, Frank, in typical Bascombe fashion, faces down the mortality that is assured each of us, and in doing so confronts what happiness might signify at the end of days. In this memorable novel, Richard Ford puts on displays the prose, wit, and intelligence that make him one of our most acclaimed living writers. Be Mine is a profound, funny, poignant love letter to our beleaguered world"--

The bezzle (Martin Hench, 2, 1, 2024)
The year is 2006. Martin Hench is at the top of his game as a self-employed forensic accountant, a veteran of the long guerrilla war between people who want to hide money, and people who want to find it. He spends his downtime on Catalina Island, where scenic, imported bison wander the bluffs and frozen, reheated fast food burgers cost twenty-five dollars. Wait, what? When Marty disrupts a seemingly innocuous scheme during a vacation on Catalina Island, he has no idea he's kicked off a chain of events that will overtake the next decade of his life. Martin has made his most dangerous mistake yet: trespassed into the playgrounds of the ultra-wealthy and spoiled their fun. To them, money is a tool, a game, and a way to keep score, and they've found their newest mark--California's Department of Corrections. Secure in the knowledge that they're living behind far too many firewalls of shell companies and investors ever to be identified, they are interested not in the lives they ruin, but only in how much money they can extract from the government and the hundreds of thousands of prisoners they have at their mercy. A seething rebuke of the privatized prison system that delves deeply into the arcane and baroque financial chicanery involved in the 2008 financial crash, The Bezzle is a sizzling follow-up to Red Team Blues.